Are Asian hands more flexible than their Caucasian counterparts?. (September 2013) - Shahid, Mohammad; Mahroof, Sabreena; Wu, Feiran; Bourne, Kathryn; Jose, Rajive; Titley, Garth
Introduction: Though there is a general perception that Asian hands have an increased range of movements in all their joints, there is very little written in the literature on this topic. Our unit caters to a multiethnic population and it has been our experience that the outcomes after hand surgery are generally better in Asian hands. This study was aimed at comparing the range of movements between two cohorts of volunteers: Asians and Caucasians. Methods: Data were collected on their ethnicity, gender, age, handedness and any medical conditions. The Beighton score was measured for all subjects and range of movements was measured using a standard goniometer. Totally, 114 subjects were enrolled into the study, which included 53 men (46%). Results: There were 59 Caucasians and 55 Asians. The range of movements of wrist and hand was greater in Asians and the difference was statistically significant ( p  < 0.05). Men in general had greater range of movement of the fingers whereas women had greater range of movement of the thumb. There was no difference between Asian men and women with regard to wrist movements. However, Caucasian women had greater wrists movements than Caucasian males. The average Beighton score was the highest in Asian women (7), followed by Asian men (6). Caucasian men and women had an average Beighton Score of 2. Discussion: Normative data for different ethnic groups are important for hand therapy as they can guide rehabilitation protocols. Our study demonstrates that a difference in hand flexibility between British Asians and their Caucasian counterparts exists.